2015
DOI: 10.1111/anae.13275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel Surgicric® cricothyroidotomy device for emergency tracheal access in a porcine model

Abstract: SummaryA can't intubate, can't ventilate scenario can result in morbidity and death. Although a rare occurrence (1:50 000 general anaesthetics), it is crucial that anaesthetists maintain the skills necessary to perform cricothyroidotomy, and are well‐equipped with appropriate tools. We undertook a bench study comparing a new device, Surgicric®, with two established techniques; the Melker Emergency Cricothyroidotomy, and a surgical technique. Twenty‐five anaesthetists performed simulated emergency cricothyroido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
4
14
0
2
Order By: Relevance
“…Although we showed a difference in speed of securing an airway with a palpable vs. an impalpable membrane, the timings for the latter were still acceptable, demonstrating the positive effect of training. Both sets of times are comparable to those found by other groups investigating broadly similar bougie-assisted cricothyroidotomy techniques [10][11][12][13], with average procedural times of 33-81 s. Our study, however, is probably the first evaluation of the FONA techniques described in the DAS 2015 guidelines in a benchtop study and showed a high first-attempt success rate.…”
Section: Discussionsupporting
confidence: 85%
“…Although we showed a difference in speed of securing an airway with a palpable vs. an impalpable membrane, the timings for the latter were still acceptable, demonstrating the positive effect of training. Both sets of times are comparable to those found by other groups investigating broadly similar bougie-assisted cricothyroidotomy techniques [10][11][12][13], with average procedural times of 33-81 s. Our study, however, is probably the first evaluation of the FONA techniques described in the DAS 2015 guidelines in a benchtop study and showed a high first-attempt success rate.…”
Section: Discussionsupporting
confidence: 85%
“…The median time of 90 s (when successful) for participants to achieve scalpel‐bougie eFONA is similar to the time to achieve cricothyroidotomy in several benchtop model studies and a wet lab study .…”
Section: Discussionsupporting
confidence: 55%
“…Although there was an added step of inserting the introducer following scalpel incision, the insertion times were significantly faster in this simulated obese model. However, the times taken in this study was longer and required more insertion attempts compared with the cricothyroidotomy studies previously conducted in our institution on a similar porcine model, but with only a thin overlying layer of skin. This correlates with the knowledge that cricothyroidotomy is technically more challenging and demanding in obese subjects, as observed in a previous simulated obese neck study .…”
Section: Discussionmentioning
confidence: 78%
“…We calculated that we would need a sample size of at least 25 participants to show whether the insertion times for a pair of devices differed by more than a threshold value of 45 s and standard deviation of difference of around 80, using a two‐sided, 5% significance level and 80%, based on two studies comparing cricothyroidotomy techniques conducted in our institution . We used the Wilcoxon matched pairs signed‐rank test to analyse the results (non‐normal distributions) and the McNemar test to compare the success rate, occurrence of false passage and identification of cricothyroid membrane.…”
Section: Methodsmentioning
confidence: 99%